Terahertz active multi-channel vortices with parity symmetry breaking and near/far field multiplexing based on a dielectric-liquid crystal-plasmonic metadevice - Yiming Wang; Fei Fan; Huijun Zhao; Yunyun Ji; Jing Liu; Shengjiang Chang (Opto-Electronic Advances)
Vortex beams carrying orbital angular momentum (OAM) are of great significance for high-capacity communication and super-resolution imaging. However, there is a huge gap between the free-space vortices (FVs) and plasmonic vortices (PVs) on chips, and active manipulation as well as multiplexing in more channels have become a pressing demand. In this work, we demonstrate a terahertz (THz) cascaded metadevice composed of a helical plasmonic metasurface, a liquid crystal (LC) layer, and a helical dielectric metasurface. By spin-orbital angular momentum coupling and photon state superposition, PVs and FVs are generated with mode purity of over 85% on average. Due to the inversion asymmetric design of the helical metasurfaces, the parity symmetry breaking of OAM is realized (the topological charge numbers no longer occur in positive and negative pairs, but all are positive), generating 6 independent channels associated with the decoupled spin states and the near-/far- field positions. Moreover, by the LC integration, dynamic mode switching and energy distribution can be realized, finally obtaining up to 12 modes with a modulation ratio of above 70%. This active tuning and multi-channel multiplexing metadevice establishes a bridge connection between the PVs and FVs, exhibiting promising applications in THz communication, intelligent perception, and information processing.